The Impact of the Information Security Systems on the institutional Excellence Achievement in the Jordanian Universities - Ibrahem, Sadeiq Blal; El Amin, Abdel Rahman Mohamed; Awadallah, Ahmed Hosny (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to identify the impact of the information Security Systems on the institutional Excellence Achievement in the Jordanian universities, were the study community consisted of all the Jordanian universities employees who uses Information Technology in all the (26) public and private universities. The study sample consisted of users of information technology in the Jordanian universities‎; the study sample represented the three main regions in Jordan (North, Central and South). A questionnaire was distributed to the sample members; the analytical descriptive approach has been used because it suits the current study. The study found that the dimensions of Information Systems scored generally high; were the availability and confidentiality variables scored high, the integration variable scored medium. The organizational Excellency dimensions scored generally medium, The results showed a statistically significant impact of information security systems (confidentiality, integration and availability) on institutional excellence in Jordanian universities.